Chemical screening of guggul (Commiphora wightii) accessions collected from different natural habitats of Gujarat (Open Access Journal of Medicinal and Aromatic Plants, 2011)
(Abstract selected from presentation in National Conference on Biodiversity of Medicinal and Aromatic Plants: Collection, Characterization and Utilization, held at Anand, India during November 24-25, 2010) Guggul (Commiphora wightii) is naturally distributed in the drier tracts of Gujarat. In the present study twenty six accessions collected from different part of Gujarat was used for chemical screening. Guggulsterone-Z, is an important secondary metabolite of C. wightii. Determination of guggulsterone-Z was conducted by High performance Liquid chromatography method. Chromatographic separation was achieved on a C18 column using mobile phase water– acetonitrile system. Detection was set at UV wavelength of 242 nm. The ethyl acetate extract of dried stem bark evaporated and dissolved in methanol used for HPLC analysis. The content of guggulsterones-Z was determined in stem bark of Gujarat collection. Guggulsterone-Z varied greatly among the accession and its range was 0.05± 0.01% to 0.92± 0.24 %. Percentage of guggulsterone-Z was lowest in Guj 15 and it was highest in Guj 2. The screening was done based on the sex of the plant also. It was found that among the females, guggulsterone-Z content varied from 0.09± 0.01 (Guj 1) to 0.92± 0.24 (Guj 2). Among the hermaphrodites, it ranged from 0.05± 0.01 (Guj 15) to 0.64± 0.00 (Guj 6) and among the males, guggulsterone-Z content varied from 0.08± 0.02 (Guj 16) to 0.55± 0.11 (Guj 17).